Forest fire hazard assessment based on forest typology - Volodymyr P. Voron; Andriy D. Kuzyk; Sergiy V. Ivashyniuta; Yilia R. Tsipan (Наукові праці Лісівничої академії наук України)
The study of forest fire prevalence in Ukraine in recent years has revealed severe challenges for the scientific community associated with the reduction of operational, nature protection, and recreational functions of forests. When assessing the potential fire hazards, a contradiction arises because the fire risk is minimal in wet hygrotopes, but on the other hand, the total supply of terrestrial combustible materials is greater in forest types with excessive soil moisture, where organic matter decomposes. In these conditions, along with the accumulation of fallen needles and branches, an important factor in the fire hazard is also the role of the live ground cover. It has been found that the development of new methodology for assessing fire danger is of significant importance for effective prevention of forest fires, which should be based not only on physical principles of fire break-out and spread but also on forest site conditions. One of the key aspects is examination the forest types in Ukraine and their relationship with the risk of forest fires. Based on experimental studies, the inflammability of herbaceous and moss plants within the Small Polissia region has been identified. Fire-prone species include 14 herbaceous plants from the Poaceae family (Dactylis glomerata L., Koeleria glauca (Spreng.) DC., Stipa johannis Cel., Festuca ovina L., Calamagrostis epigeios (L.) Roth., Dianthus arenarius L., Calamagrostis arundinacea (L.) Roth, Brachypodiun pinnatum P.B., Molinia caerulea (L.) Moench, Melica nutans L., Milium effusum L., Phleum phleoides Sm., Poa nemoralis L., Deschampsia cespitosa L.), 11 from the Cyperaceae family (Carex limosa L., Carex inflata Huds, Carex pilosa Scop., Carex acutiformis Ehrh., Carex brevicollis D.C., Carex sylvastica Huds., Carex pseudocyperus L, Carex vesicaria L., Carex lasiocarpa Ehrh., Carex melanostachya M.B., Eriophorum vaginatum L.), 4 herbaceous plants from the Ericaceae family (Vaccinium vitis-idaea L., Vaccinium uliginosum L., Vaccinium oxycoccos, Vaccínium myrtillus L.); 5 mosses (Hylocomium splendens (Hedw.) Schimp., Dicranum undulatum Ehrh., Pleurozium schreberi (Willd. Ex Brid., Ptilium crista-casterensis (Hedw.) De Not, Cetraria islandica (L.) Ach.), lichens of the genus Cladonia Nyl. and Calluna vulgaris (L.) Hill.